Perancangan Kursi Ergonomis untuk Pekerja dengan Skoliosis - Baiq Kalisa Sarah Daka; Rahmawan Dwi Prasetya; Sekar Adita (INSTITUT SENI INDONESIA PADANGPANJANG, 2026)
Scoliosis is often exacerbated by poor sitting habits, particularly during prolonged work activities. Addressing this issue, this study focuses on the design of an ergonomic office chair specifically tailored for individuals with scoliosis to help maintain proper sitting posture while enhancing comfort during work. The design approach used is the Double Diamond method, which includes the discovery, definition, development, and delivery phases. Data was collected through questionnaires and interviews with 33 adult respondents with scoliosis, as well as through a literature review on the relationship between sitting posture and the progression of scoliosis. Analysis results indicate that the primary user need—comfort—can be achieved through the use of cushioning materials and a chair design capable of adapting to the direction of spinal curvature. This design research resulted in an office chair featuring elements such as a memory foam seat that conforms to the body’s shape, and adjustable features tailored to spinal curvature.